Carbon nanotube fence-wall for radio frequency isolation - Tan, Dunlin (2016)
With an emergent need to miniaturize multifunctional radio frequency architectures, efficient designs have to be well thought. These include techniques to manage high power demands, electromagnetic compatibility between adjacent components and thermal management, in order to maintain desired performances. One way to address this is, through the use of nano-materials. However, there are many challenges faced with the use of such emerging materials, such as difficulty in implementation and effective integration into electronics. An example of such material is carbon nanotube. Carbon nanotubes have potential to be utilized in such a way due to its exemplary electrical, mechanical and thermal properties supported by both simulations and experimental data. However, like many emerging materials, there are existential issues that have to be addressed before its potential can be realized. One of the biggest challenges is synthesis compatibility with device integration, such as high temperature growth. These issues aside, a new area where carbon nanotubes could play an important role is in the area of on-circuit electromagnetic shielding. Carbon nanotubes are ideal for this due to it being light weight, electrically conductive and having high aspect ratios. This thesis is thus dedicated to the understanding of how, carbon nanotubes may be implemented into, and used to reduce electromagnetic interference in future high density components. The high growth temperature of carbon nanotube was first addressed. A stable and known synthesis technique of carbon nanotube was first evaluated. Key parameters that could affect carbon nanotube growth were identified. This was carried out using statistical design of experiment, to quantify the contribution of each parameter to the growth length of carbon nanotube. An alternate approach, termed the radiative approach was introduced. This approach allowed carbon nanotube growth to be conducted, without subjecting its substrate to high growth temperatures. This technique also allowed the substrate to remain at a lower temperature without compromising the high decomposition temperature of acetylene. As a result of systematic studies and optimization of parameters, substrate temperature of up to 420 °C was obtained, with growth length of 40 µm whilst the growth temperature remained at 600-650 °C. Raman spectroscopy was also used to examine the crystallinity of carbon nanotubes grown at low substrate temperatures. The disorder in sp2 was analyzed by the ratios of the characteristic defect and graphitic bands of carbon nanotubes. The Raman spectra observed in carbon nanotubes grown at different temperatures, and at different substrate temperature were contrasted. Next a study of how high density carbon nanotube forests, termed carbon nanotube fence-wall, were used for electromagnetic shielding was carried out. Here a new radio frequency isolation technique was demonstrated with improvement over current techniques in terms of performance and size. A full spectrum study, including design, simulation, fabrication and measurements were carried out. Passive structures made of microstrip lines and via-fences were first designed using Ansys full wave solver HFSS. A carbon nanotube bulk model that took into account the physical, geometrical and electrical properties of CNTs was used and implemented into the design in HFSS. S-parameters were simulated. Parametric studies were carried out by simulations, to identify factors that had effects on the electromagnetic shielding effectiveness of carbon nanotubes. Various test structures based on silicon, alumina and printed circuit boards were fabricated based on key simulation data. A variety of substrates were used, to take into account low cost applications, ease of implementation, substrate temperature budget and industrial needs. Here, 10 dB improvement in RF isolation was demonstrated, with 80 % reduction in lateral dimension as compared to the classical via-fencing technique. In this proof of concept, the simulation and measurement results were well correlated. In addition, measurements have also shown that, isolation attainable by the carbon nanotube fence-wall was comparable with that of bulk metal. Variants of the carbon nanotube fence-wall such as channelized fence and cavity were tested, to demonstrate different ways in which it may be implemented into electronic packages for electromagnetic shielding. The implication is, a potential light weight electromagnetic shield made of carbon nanotube that may be integrated into future systems. All in all, electromagnetic compatibility using carbon nanotubes for electronic package was studied. Some challenges faced by implementation of carbon nanotubes into nano-packages have been identified and dealt with. A possible solution to mitigate electromagnetic interference in next generation light-weight radio frequency components and applications has been proposed.